RAGAM ORNAMEN PADA POT GERABAH STUDI KASUS DI INDUSTRI KERAJINAN NARWAN KERAMIK - Sudarman, Tria; Nurcahyanti, Desy (Amerta Media, 2024)
Indonesia has many pottery-producing regions that have different characteristics. One of the pottery producing areas is Sayangan Hamlet, Melikan Village, Klaten Regency. The majority profession of the people of Sayangan Hamlet is as pottery craftsmen. The people of Sayangan Hamlet have a pottery handicraft industry, one of which is Narwan Keramik. The products produced by Narwan Keramik are products made using the press molding technique. One of them is an earthenware pot, the production of pottery pots produced is an ornamental pottery pot. Product pottery products that are identical to the application of ornaments on the walls of pottery with the aim of adding aesthetic value. This research discusses the visualization of ornamental pots and describes the production process of pottery pots with the addition of ornaments. The method used in this research is qualitative research method with case study. The data collection technique used in this research is data reduction, data presentation and data analysis. data reduction techniques, presenting data and drawing conclusions. To strengthen validity of the data, data triangulation was carried out. The results of this research can The results of this research can show the works of various ornaments applied to pottery pots and the process of producing pottery pots by doing several stages, namely: 1.stages of producing pottery pots by doing several stages, namely: preparation (design idea), design validation, product realization. Keywords: Pottery, ornament, pot, variety. Indonesia memiliki banyak daerah-daerah penghasil gerabah yang memiliki karakteriatik berbeda-beda. Salah satu daerah penghasil gerabah yaitu Dusun Sayangan, Desa Melikan Kabupaten Klaten. Profesi mayoritas masyarakat Dusun Sayangan adalah sebagai pengrajin gerabah. Mayarakat Dusun Sayangan memiliki industri kerajinan gerabah, salah satunya Narwan Keramik. Produk yang diproduksi Narwan Keramik merupakan produk yang dibuat menggunakan Teknik cetak tekan. Salah satunya pot gerabah, produksi pot gerabah yang dihasilkan merupakan pot gerabah hias. Produk pot gerabah yang identik dengan pengaplikasian ornamen pada dinding gerabah dengan tujuan untuk menambah nilai estetik. Penelitian ini membahas visualisasi ragam hias ornamen pot gerabah dan mendeskripsikan proses produksi pot gerabah dengan penambahan ornamen. Metode yang digunakan pada penelitian ini adalah metode penelitian kualitatif dengan studi kasus. Teknik pengumpulan data yang digunakan dalam penelitian ini dengan menggunakan teknik reduksi data, penyajian data dan menarik kesimpulan. Untuk memperkuat keabsahan data, dilakukan tringgulasi data. Hasil penelitian ini dapat menunjukkan karya-karya ragam ornamen yang diaplikasikan pada pot gerabah dan proses tahapan memproduksi pot gerabah dengan melakukan beberapa tahapan yaitu: persiapan (ide desain), validasi desain, perwujudan produk. Kata kunci: Gerabah, ornamen, pot, ragam.